Controllable synthesis of a novel magnetic core–shell nanoparticle for dual-modal imaging and pH-responsive drug delivery. (15th November 2017) - Xu, Chen; Zhang, Cheng; Wang, Yingxi; Li, Liu; Li, Ling; Whittaker, Andrew K
Abstract: In this study, novel magnetic core–shell nanoparticles Fe3 O4 @La-BTC/GO have been synthesized by the layer-by-layer self-assembly (LBL) method and further modified by attachment of amino-modified PEG chains. The nanoparticles were thoroughly characterized by x-ray diffraction, FTIR, scanning electron microscopy and transmission electron microscopy. The core–shell structure was shown to be controlled by the LBL method. The drug loading of doxorubicin (DOX) within the Fe3 O4 @La-BTC/GO-PEG nanoparticles with different numbers of deposited layers was investigated. It was found that DOX loading increased with increasing number of metal organic framework coating layers, indicating that the drug loading can be controlled through the controllable LBL method. Cytotoxicity assays indicated that the Fe3 O4 @La-BTC/GO-PEG nanoparticles were biocompatible. The DOX was released rapidly at pH 3.8 and pH 5.8, but at pH 7.4 the rate and extent of release was greatly attenuated. The nanoparticles therefore demonstrate an excellent pH-triggered drug release. In addition, the particles could be tracked by magnetic resonance imaging (MRI) and fluorescence optical imaging (FOI). A clear dose-dependent contrast enhancement in T 2 -weighted MR images and fluorescence images indicate the potential of these nanoparticles as dual-mode MRI/FOI contrast agents.